Energy saving as a basis for competitiveness of oil and fat products industry enterprises - Попов, Микола Олексійович (Technology audit and production reserves, 2013)
The increase of potential of capacity of processing of oilseeds caused the increase of production of oil and fat products. However, high amount of oil and fat products at the Ukrainian and world market is accompanied by strong competition, so it makes manufacturers seek for ways of their improvement. Despite the numerous developments aimed to increase the competitiveness of enterprises of oil and fat products industry, the issue is relevant and has strategic importance. In particular, the issue of energy consumption in the structure of production costs, practically neglected, is worth noting. Therefore, based on the above, the main purpose of the article is to identify the impact of energy consumption on the competitiveness of oil and fat products. As part of the study, it was determined that the cost of heat and electricity in the structure of production costs tend to increase, thus reducing the competitiveness of products. In the article, the author proposed main potential energy saving areas, the implementation of which will reduce energy costs and ensure competitive advantages of products at home and foreign market.